2005
DOI: 10.1577/m04-192.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Survival of Wild and Hatchery‐Origin Winter Steelhead Spawners Caught and Released in a Recreational Fishery

Abstract: Mandatory catch and release of wild fish and supplementation with hatchery-reared fish are commonly used to sustain sport fisheries on low-abundance populations of wild steelhead. However, their effectiveness in limiting angling mortality on wild fish is uncertain. We radiotagged 226 (125 wild, 101 hatchery) angled adult steelhead Oncorhynchus mykiss near the mouth of the VedderϪChilliwack River, British Columbia, in 1999 and 2000 and monitored their subsequent movements to determine survival to spawning and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 37 publications
4
45
1
Order By: Relevance
“…Nelson et al. () used radiotelemetry to describe the distribution of prespawning wild and hatchery steelhead in the Vedder–Chilliwack River, British Columbia. They found considerable overlap in the spatial distributions of wild and hatchery steelhead.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nelson et al. () used radiotelemetry to describe the distribution of prespawning wild and hatchery steelhead in the Vedder–Chilliwack River, British Columbia. They found considerable overlap in the spatial distributions of wild and hatchery steelhead.…”
Section: Discussionmentioning
confidence: 99%
“…; Dittman and Quinn ; Nelson et al. ). Also, the amount of time that hatchery smolts spend in the river prior to emigrating to the ocean influences their ability to home to their release site (Keefer and Caudill ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacific salmon captured and released in the ocean have been shown to experience much higher postcapture and release mortality rates: 33-55% for purse-seine-caught Sockeye Salmon , 44% for troll-caught Coho Salmon (Parker et al 1959), and up to 75% for Coho Salmon captured by gill net (Buchanan et al 2002). During river migration, most studies of capture mortality have focused on recreational angling, with mortality estimates ranging from 1% to 69% depending on species, study location, duration of postrelease monitoring, and research techniques (Bendock and Alexandersdottir 1993;Vincent-Lang et al 1993;Vander Haegen et al 2004;Nelson et al 2005;Cowen et al 2007;Raby et al 2012). Recent biotelemetry research revealed that angled and released Sockeye Salmon migrating up the lower Fraser River were 20-35% less likely to reach spawning areas than individuals tagged in the ocean and subsequently tracked in freshwater (Donaldson et al 2011, in press).…”
Section: Discussionmentioning
confidence: 99%
“…The fate of this latter group is unknown. Fishing by gillnets or hand‐held gear greatly influences rates of mortality for released farmed salmonids (Nelson et al , 2005; Baird et al , 2006), thus the fishing mortality recorded in the present study was probably an underestimate.…”
mentioning
confidence: 82%